Problems encountered and coping strategies of the male gay students at the College of Nursing - Maranda, Jiddo Andrei G. (Lasallian Research Forum, 2009)
This study sought to explore in depth the problems encountered by the gay college students, how they face these issues, their views about themselves, and the overall impact of these experiences. The researcher employed a qualitative research design and incorporated the tools of a case study. Specifically, in using this in-depth method the researcher operated through focused and structured individual interview questionnaire in exploring the participants' responses.